Uroflowmetry before and After Transurethral Resection of Prostate for Bladder Outlet Obstruction - Rahman, MH; Islam, MA; Joarder, AI; Mannan, M; Bhuiyan, MR; Paul, BK (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):601-7 The abstract of this article is available on the PubMed website